The pseudopterosins: anti-inflammatory and analgesic natural products from the sea whip Pseudopterogorgia elisabethae. - Look, S A (1986)
The Caribbean sea whip Pseudopterogorgia elisabethae (Octocorallia, Cnidaria) has been found to contain the pseudopterosins, a newly described class of natural products, which have been characterized as diterpene-pentoseglycosides. The pseudopterosins possess anti-inflammatory and analgesic properties that exceed, in our assays, the potencies of existing drugs such as indomethacin. As anti-inflammatory agents, the pseudopterosins appear to modify the arachidonic acid cascade by an as yet undefined mechanism of pharmacological action.